Enhancing Student Outcomes in Acid-Base Titration Through Assessment for Learning - Ningtryas, Klara Dinda Ayu; Muchlis, Muchlis; Harahap, Ilham Pradana Putra (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
The purpose of this study was to describe the implementation of assessment for learning-oriented learning and learning outcomes on acid-base titration material in class XI. This research was conducted in class XI-1 and XI-5 SMA Giki 1 Surabaya. The results showed that the implementation of assessment for learning-oriented learning on acid-base titration material as a whole received very good criteria. This is evidenced by the average percentage of implementation scores at the first meeting of 99.3% and 98.5% for classes XI-1 and XI-5, as well as the second meeting of 99% and 99.5% in classes XI-1 and XI-5 with the criteria for each meeting is very good. Learning outcomes through assessment applications for learning-oriented learning have increased in one sample t-test. The test found that posttest2 XI-5 - posttest2 XI-1 in both classes got a p-score> 0.05, then Ho was accepted, and Ha was rejected. Thus, the score for posttest 2 XI-1 was smaller than that of posttest 2 XI-5. There is no significant difference in posttest 2 between the two classes. So from this, it can be concluded that learning that applies the Assessment for Learning-oriented student worksheet is effective even though the average results of the two classes show differences.